Implementing web-based e-scaffolding enhances learning (ESEL) at the center of mass conceptual understanding - Lia Laela Sarah; Yudi Ananto; Dona Octonary; Lissiana Nussifera (Jurnal Inovasi Pendidikan IPA, 2022)
Many online learning models are alternatives due to the Covid-19 pandemic in synchronous, asynchronous, or mixed-mode. However, resources to support independent student learning in Indonesia were still limited. The focus topic of the study is developing students' understanding of the physics concept of center of mass. A Web-based E-Scaffolding Enhance Learning (ESEL) was identified and implemented. This study used a quasi-experiment, one group, pretest-posttest design. Forty-one students participated in the research. The ESEL model involved four phases: sense-making, process management, articulation, and reflection. Students undertook ESEL-based activity developed for the online asynchronous mode implementation. In addition, synchronous meetings and sharing of learning results using an online platform. Data analysis shows that the web-based ESEL model supported online learning of the center of mass concept, though some improvements are possible. Specifically, learning outcomes increased with a significant value increase between the pre-test and post-test, and a normalized gain score of 0.73 indicated effective learning in high criteria. This research shows that the web-based ESEL approach is an effective self-directed learning tool for online physics classrooms.